It's Now Or Never! Using Deadlines as Nudges. Issue 3 (12th May 2016) - Zamir, Eyal; Lewinsohn‐Zamir, Daphna; Ritov, Ilana
Abstract : Incorporating behavioral insights into regulation is plausibly the most significant development in regulatory theory and practice in recent years. Behaviorally informed regulation encourages self‐benefiting and socially desirable behaviors with little intrusion on autonomy. Drawing on new empirical findings, this article puts forward the hitherto overlooked possibility of employing the deadline effect as a regulatory tool. Deadlines serve as an antidote to procrastination and forgetfulness. Many empirical and experimental studies have examined the use of deadlines in marketing. This study explores the possible use of deadlines by legal policy makers. It describes two survey experiments, a randomized field experiment and a natural experiment, which suggest that deadlines may encourage self‐benefiting and socially desirable behaviors, and that relaxing deadlines may discourage less desirable behavior. The article discusses the practical and normative aspects of using deadlines as a regulatory means, compared to alternative tools, such as default rules and required choices.